2022
DOI: 10.1007/s11146-022-09909-w
|View full text |Cite
|
Sign up to set email alerts
|

The Valuation Effect and Consequences of Clawback Adoption in Real Estate Investment Trusts

Abstract: This study explored the valuation effect of clawback adoption in the REIT market and identified possible channels through which clawback may generate benefits to REITs.We first found that the stock market reacts positively to the announcement of clawback adoption, and that market response is more pronounced when the clawback policy is strong, based on a sample of initial clawback adoptions in REITs between 2007 and 2018. The valuation effect of clawback adoption is stronger among those REITs with higher likeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…As mentioned above, one limitation to use the propensity score approach is the small sample size after matching. We applied an entropy balancing approach (Hainmueller [48]; Peng, Shen, Fung, Hui and Fan [49]) by matching rated REITs to weighted unrated REITs on a continuous scale. The results from the entropy balancing approach also indicated that after the introduction of credit ratings, REITs significantly increased debt ratio and debt maturity and reduced equity financing and cash holdings.…”
Section: Further Discussion and Robustness Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, one limitation to use the propensity score approach is the small sample size after matching. We applied an entropy balancing approach (Hainmueller [48]; Peng, Shen, Fung, Hui and Fan [49]) by matching rated REITs to weighted unrated REITs on a continuous scale. The results from the entropy balancing approach also indicated that after the introduction of credit ratings, REITs significantly increased debt ratio and debt maturity and reduced equity financing and cash holdings.…”
Section: Further Discussion and Robustness Testsmentioning
confidence: 99%
“…In the robustness tests, we also applied another matching method, namely the entropy balancing approach, following Hainmueller [48] and Peng, Shen, Fung, Hui and Fan [49]. One limitation of the propensity score matching approach is that the sample size is reduced substantially after the matching.…”
Section: Methodsmentioning
confidence: 99%